(untitled) (Ciudades, 2017)
The prominence of the region as preferred scale for spatial planning enables the definition of new instruments, models and administrative structures for managing the territorial policies. The combination and modulation of these instruments defines the “style” of european planning systems. In this paper we analyse how the complex interplay between the different levels of supra-local planning is solved to increase the efficiency of territorial policies. For this purpose, we conducted a case study of the territorial planning in the Central Counties of Catalonia, during two recent legislative sessions (2003-2010). In this case, the dialogue between the different levels of supramunicipal planning is analogous to the relationship between the general and sector planning. These physical plans confirm the instrumental coherence between the different scales of a common territorial model.